A rare case of fourth consecutive fallopian tube ectopic pregnancy - Pandey, Divya; Nagar, Teena; Sharma, Shakti; Salhan, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We present a case of consecutive fourth tubal ectopic in a patient which was managed by emergency laparotomy and salpingectomy. The first two tubal ectopic pregnancies occurred on the right side while the subsequent two occurred on the contralateral side. The patient was planned for IVF-ET.